Las Animas Chapter Of The Rocky Mountain Coal-Mining Institute (Rocky Mountain Coal Mining Institute, 1913)
John P. Thomas, President. B. W. Snodgrass, Secretary-Treasurer. San Andrews, mine boss, Morley. Richard Bickerton, Tabasco. E. P. Bayles, superintendent, Cokedale. Clyde Campion, parting tender, Valdez. O. C. Cook, 406 East Seventh, Street, Trinidad. James Cameron, superintendent, Hastings. Charles Chambers, superintendent, ,Sopris. Arthur Dennison, Trinidad. Samuel Dean, mine inspector, Delagua. F. S. Dunlevy, assistant engineer, Hastings. L. R. Douglas, assistant engineer, care Danford & Sanderson, Trinidad. W. E. Danford, superintendent, Segundo. M. O. Danford, superintendent, Cedar Hill Coal & Coke Co., Trinidad. John Dougherty, mine foreman, Morley. J. C. Davidson, timberman, Valdez. William Easton, fire boss, Valdez. George Fortune, electrician, Primero. D. J. Griffiths, chief mine inspector, Trinidad. J. E. Hanes, assistant engineer, Hastings. Joseph Haske, superintendent, Primero. O. C. Erwin, electrician, 714 Pine Street, Trinidad. R. J. Jinkins, superintendent, Morley. Thomas jolly, superintendent, Gray Creek. James Jamieson, assistant mine boss, Valdez. James Kilpatrick, fire boss, Tobasco. L. M.. Kuhns, first-aid miner, care Mine Safety Car No. 2, Trinidad. William B. Lloyd, 404 East Seventh Street, Trinidad. J. C. Lawrence, machinist, Starkville. R. A. McAllister, mine inspector, Trinidad.